Structural Determinants of Homicide: The Big Three - Tcherni, Maria (Journal of quantitative criminology, 2011)
Building upon and expanding the previous research into structural determinants of homicide, particularly the work of Land, McCall, and Cohen ( 1990 ), the current paper introduces a multilevel theoretical framework that outlines the influences of three major structural forces on homicidal violence. The Big Three are poverty/low education, racial composition, and the disruption of family structure. These three factors exert their effects on violence at the following levels: neighborhood/community level, family/social interpersonal level, and individual level. It is shown algebraically how individual-level and aggregate-level effects contribute to the size of regression coefficients in aggregate-level analyses. In the empirical part of the study, the presented theoretical model is tested using county-level data to estimate separate effects of each of the Big Three factors on homicide at two time periods: 1950–1960 and 1995–2005 (chosen to be as far removed from one another as the availability of data allows). All major variables typically used in homicide research are included as statistical controls. The results of analyses show that the effects of the three major structural forces—poverty/low education, race, and divorce rates—on homicide rates in US counties are remarkably strong. Moreover, the effect sizes of each of the Big Three are found to be identical for both time periods despite profound changes in the economic and social situation in the United States over the past half-century. This remarkable stability in the effect sizes implies the stability of homicidal violence in response to certain structural conditions.